'I start again with every story, listening': Sound, silence and voice in two short stories by David Constantine. Issue 1 (1st June 2021) - Görtschacher, Wolfgang
This article examines sound and the sonic aspects of voice and silence in two short stories by David Constantine ‐ 'Tea at the Midland' and 'Under the Dam' ‐ to show that they are not only relevant for an analysis of his poetry but also for his short stories. Employing Jonathan Sterne's definition of sonic culture as a theoretical starting point, the phonotextual (Garrett Stewart) multiplicity of patterns in each text is seen as an alternative to the protagonists-focalizers' 'silenced' situation and is associated with their desired joys in life. In 'Tea at the Midland' the withheld soundscape (R. Murray Schafer) of the bay can only be watched but not heard. In the opening of 'Under the Dam' the auscultator (Melba Cuddy-Keane) Seth is completely oblivious of his sonic surroundings and effaces sound on the story level, but the narrator reintroduces sound on the level of discourse. Sylvia Mieszkowski's distinction between the sound of the text and the sound in the text constitutes one of the fundamental concepts of the analysis. The findings and conclusions are interpreted in the context of Constantine's own poetics as regards the writing of short stories. The sounds of the two short stories reinforce, through metrical, rhythmic, syntactic and sound patterns, the scenes' withheld sonic qualities that are only perceived visually and sensed emotionally by the protagonists. These soundscapes represent alternative worlds desired by the protagonists in 'Under the Dam' and by the woman in 'Tea at the Midland'.